Math, asked by vinayvini359, 6 months ago

In an AP the sum of first 9 term is 14 more then 5 time the 8th term 8th and 2rd term are in the ratio 11:2 find the sums of first 20 terms of the A.P​

Answers

Answered by basavaraj5392
15

ABOVE ATTACHED, I HOPE YOU SATISFIED WITH MY ANSWER.

IF YOU SATISFIED WITH MY ANSWER THEN PLEASE MARK ME AS BRAINLIEST.

Attachments:
Answered by varadad25
9

Answer:

The sum of the first 20 terms of the AP is 1180.

Step-by-step-explanation:

We have given the information about an AP.

We have to find the sum of first 20 terms of the AP.

Now,

\displaystyle{\sf\:t_8\::t_2\:=\:11\::2\:\:\quad\:\:\:-\:-\:-\:[\:Given\:]}

\displaystyle{\implies\sf\:\dfrac{t_8}{t_2}\:=\:\dfrac{11}{2}}

\displaystyle{\implies\sf\:t_8\:=\:\dfrac{11}{2}\:\times\:t_2}

\displaystyle{\implies\sf\:t_8\:=\:\dfrac{11\:t_2}{2}}

\displaystyle{\implies\sf\:t_8\:=\:\dfrac{11\:\times\:[\:a\:+\:(\:2\:-\:1\:)\:d\:]}{2}}

\displaystyle{\implies\sf\:t_8\:=\:\dfrac{11\:\times\:(\:a\:+\:d\:)}{2}}

\displaystyle{\implies\sf\:t_8\:=\:\dfrac{11a\:+\:11d}{2}\:\quad\:\:\:-\:-\:-\:(\:1\:)}

Now, we know that,

\displaystyle{\pink{\sf\:S_n\:=\:\dfrac{n}{2}\:[\:2a\:+\:(\:n\:-\:1\:)\:d\:]}\sf\:\quad\:-\:-\:-\:[\:Formula\:]}

Now, from the given condition,

\displaystyle{\sf\:S_9\:=\:5\:\times\:t_8\:+\:14}

\displaystyle{\implies\sf\:\dfrac{9}{2}\:[\:2a\:+\:(\:9\:-\:1\:)\:d\:]\:=\:5\:\times\:\left[\:\dfrac{11a\:+\:11d}{2}\:\right]\:+\:14\:\quad\:-\:-\:-\:[\:From\:(\:1\:)\:]}

\displaystyle{\implies\sf\:\dfrac{9}{2}\:(\:2a\:+\:8d\:)\:=\:\dfrac{55a\:+\:55d}{2}\:+\:14}

\displaystyle{\implies\sf\:\dfrac{18a\:+\:72d}{\cancel{2}}\:=\:\dfrac{55a\:+\:55d\:+\:28}{\cancel{2}}}

\displaystyle{\implies\sf\:18a\:+\:72d\:=\:55a\:+\:55d\:+\:28}

\displaystyle{\implies\sf\:18a\:+\:72d\:-\:55a\:-\:55d\:=\:28}

\displaystyle{\implies\sf\:18a\:-\:55a\:+\:72d\:-\:55d\:=\:28}

\displaystyle{\implies\sf\:-\:37a\:+\:17d\:=\:28\:\quad\:\:\:-\:-\:-\:(\:2\:)}

Now, we know that,

\displaystyle{\pink{\sf\:t_n\:=\:a\:+\:(\:n\:-\:1\:)\:\times\:d}\sf\:\quad\:-\:-\:-\:[\:Formula\:]}

Now,

\displaystyle{\sf\:t_8\::t_2\:=\:11\::2\:\:\quad\:\:\:-\:-\:-\:[\:Given\:]}

\displaystyle{\implies\sf\:\dfrac{t_8}{t_2}\:=\:\dfrac{11}{2}}

\displaystyle{\implies\sf\:\dfrac{a\:+\:(\:8\:-\:1\:)\:d}{a\:+\:(\:2\:-\:1\:)\:d}\:=\:\dfrac{11}{2}}

\displaystyle{\implies\sf\:\dfrac{a\:+\:7d}{a\:+\:d}\:=\:\dfrac{11}{2}}

\displaystyle{\implies\sf\:2\:(\:a\:+\:7d\:)\:=\:11\:(\:a\:+\:d\:)}

\displaystyle{\implies\sf\:2a\:+\:14d\:=\:11a\:+\:11d}

\displaystyle{\implies\sf\:14d\:-\:11d\:=\:11a\:-\:2a}

\displaystyle{\implies\sf\:3d\:=\:9a}

\displaystyle{\implies\sf\:d\:=\:\dfrac{\cancel{9}\:a}{\cancel{3}}}

\displaystyle{\implies\boxed{\sf\:d\:=\:3a}\sf\:\quad\:-\:-\:-\:(\:3\:)}

Now, by substituting d = 3a in equation ( 2 ), we get,

\displaystyle{\sf\:-\:37a\:+\:17d\:=\:28\:\quad\:\:\:-\:-\:-\:(\:2\:)}

\displaystyle{\implies\sf\:-\:37a\:+\:17\:\times\:3a\:=\:28}

\displaystyle{\implies\sf\:-\:37a\:+\:51a\:=\:28}

\displaystyle{\implies\sf\:14a\:=\:28}

\displaystyle{\implies\sf\:a\:=\:\cancel{\dfrac{28}{14}}}

\displaystyle{\implies\boxed{\red{\sf\:a\:=\:2}}}

Now, we know that,

\displaystyle{\pink{\sf\:S_n\:=\:\dfrac{n}{2}\:[\:2a\:+\:(\:n\:-\:1\:)\:d\:]}\sf\:\quad\:-\:-\:-\:[\:Formula\:]}

\displaystyle{\implies\sf\:S_{20}\:=\:\dfrac{20}{2}\:[\:2a\:+\:(\:20\:-\:1\:)\:d\:]}

\displaystyle{\implies\sf\:S_{20}\:=\:10\:(\:2a\:+\:19d\:)}

\displaystyle{\implies\sf\:S_{20}\:=\:10\:(\:2a\:+\:19\:\times\:3a\:)\:\quad\:-\:-\:-\:[\:From\:(\:3\:)\:]}

\displaystyle{\implies\sf\:S_{20}\:=\:10\:\times\:(\:2a\:+\:57a\:)}

\displaystyle{\implies\sf\:S_{20}\:=\:10\:\times\:59a}

\displaystyle{\implies\sf\:S_{20}\:=\:10\:\times\:59\:\times\:2}

\displaystyle{\implies\sf\:S_{20}\:=\:590\:\times\:2}

\displaystyle{\implies\underline{\boxed{\red{\sf\:S_{20}\:=\:1180}}}}

The sum of the first 20 terms of the AP is 1180.

Similar questions